The importance of postprandial glycemic control: optimizing add-on therapy to basal insulin. Issue 1 (2nd January 2016) - Shaefer, Charles F.; Anderson, John
Abstract: Diabetes, mainly type 2 diabetes mellitus (T2DM), is associated with a growing clinical and economic burden in the United States, which is expected to increase in association with an aging population. Sufficient glycemic control in patients with T2DM, in order to reduce the risk of micro- and macrovascular complications associated with diabetes, is mediated by lifestyle modifications and a regimen of increasingly intensive antidiabetes drugs. Several treatments and strategies are available for primary care physicians to select from when choosing the most appropriate therapy for their individual patients with T2DM, but, ultimately, due to the progressive nature of the disease, most of these patients will require insulin therapy to maintain glycemic control. Regimens containing basal and postprandial insulins are widely used, but there is still widespread reluctance to initiate insulin treatment due to fear of weight gain and hypoglycemia. Furthermore, as patients approach recommended glycated hemoglobin targets, postprandial hyperglycemia becomes the main contributor to hyperglycemic exposure, necessitating the timely initiation of prandial treatment. Finally, insulin treatment can be limited by factors like the number of injections, mealtime restrictions, complex titration algorithms and patient adherence. Recent developments in antidiabetes drug research have brought more convenient basal and postprandial regimens closer. Clinical evaluation of the efficacy and safety of basal insulins plus add-on glucagon-like peptide-1 receptor agonists (GLP-1 RAs) has yielded promising results. Primary care physicians are continually challenged to optimize insulin treatment strategies to maximize patient outcomes. Emerging strategies such as long-acting basal insulin analogs and short-acting GLP-1 RAs are particularly appealing to address this challenge.